Does Experience Matter? Paramedic Cardiac Resuscitation Experience Effect on Out-of-Hospital Cardiac Arrest Outcomes. (4th May 2018) - Weiss, Nicholas; Ross, Elliot; Cooley, Craig; Polk, Joan; Velasquez, Christopher; Harper, Stephen; Walrath, Benjamin; Redman, Theodore; Mapp, Julian; Wampler, David
Abstract: Objective : Outcomes of Out-of-Hospital Cardiac Arrest (OHCA) are influenced by many factors. We postulate that paramedics who have participated in a greater number of OHCA resuscitations will have improved patient outcomes when compared to paramedics who participated in fewer resuscitations.Methods : We conducted a retrospective analysis of prospectively collected data abstracted from the cardiac arrest database of a large urban EMS system. All OHCA cases where resuscitation was attempted during the year 2014 were reviewed. Our outcome of interest was the rate of sustained Return of Spontaneous Circulation (ROSC), which is defined as ROSC for five continuous minutes or greater. The rate of sustained ROSC was calculated from cases when paramedics served in the role of the lead medic. These rates were then analyzed using the Chi-Square test.Results : A total of 1, 145 cases of OHCA met criteria for inclusion in this study, of which 343 paramedics participated in at least one cardiac arrest in 2014. The median number of resuscitations was 10 with a range from 1 to 26 resuscitations. The paramedics were dichotomized into two groups; those who participated in <10 OHCAs (120/343), labeled "less experienced, " and those who participated in ≥10 OHCAs (223/343), labeled "more experienced." Paramedics in the less experienced group had a sustained ROSC rate of 22.2% for resuscitations in which they were the lead medic, while those in the more experienced group had a rate of 28.9% (p-value = 0.047), RR 1.30 (95% CI 1.001, 1.692).Conclusions : This study demonstrated that more experienced paramedics had a statistically significant increase in achieving sustained ROSC when they were functioning in a lead role compared to less experienced paramedics. We found no other clinically significant patient outcomes related to the provider's experience.